Effects of chronic ethanol feeding on serum lipoprotein metabolism in the rat - Baraona, Enrique (1970)
In rats, chronic ethanol feeding was found to enhance the postprandial hyperlipemia and to increase the incorporation of dietary palmitic acid-(3)H and intravenously injected L-lysine-(14)C into serum lipoproteins. The main increases of total amount, labeling, and specific activity of lipid and protein occurred in the d < 1.019 lipoprotein fraction. Fat absorption and the clearance of injected chylomicrons were not affected by ethanol feeding. Blocking of lipoprotein and chylomicron removal with Triton did not prevent the action of ethanol on serum lipids, indicating that the ethanol effect is not likely due to defective removal of lipids from the circulation. Ethanol enhanced the incorporation of chylomicron fatty acids into newly synthetized very low density lipoproteins, as shown by an increased reappearance of the fatty acid label into the lipids of this fraction after injection of palmitate-(14)C/glycerol-(3)H doubly labeled chylomicrons. These results indicate that alcoholic hyperlipemia is due, at least in part, to an increase in newly synthetized lipoproteins. The hyperlipemia produced by ethanol was accompanied by hepatic steatosis. The simultaneous production of fatty liver and hyperlipemia makes it unlikely that defective lipoprotein synthesis or secretion is a primary mechanism for the pathogenesis of the alcoholic fatty liver.